PENGARUH TERAPI AKUPRESUR DALAM MENURUNKAN NYERI DISMINORE PADA REMAJA PUTRI - Firda Fibrila; M. Ridwan; Septi Widiyanti (Jurnal Penelitian Multidisiplin Ilmu, 2023)
Dysmenorrhea is menstrual pain that is felt in the lower abdomen and spread to the pelvis that can interfere with daily activities. The cause of dysmenorrhea is caused by myometrial contractions resulting in ischemia due to the prostaglandins produced by the endometrium. Type of quasi experimental research with pretest and posttest group approach. Population in this research is student of Level 1 Program Study Kebidanan Metro Poltekkes Tanjungkarang who experience dysmenorrion as much as 61 student. Sampling using simple random sampling technique as much as 53 people. Data collection using observation and interview. The univariate analysis used the mean and bivariate analysis using the dependent Willcoxon signed-rank Test statistic test. The results of the average analysis of dysmenorrhea pain in adolescent girls before being given acupressure therapy were 5.89 (moderate pain) and after acupressure therapy was obtained 3.40 (moderate pain). The result of statistical test using Willcoxon signed-rank Test obtained p value 0,000 (p ? ? 0,05), there is influence of acupressure therapy in reducing dysmenorrhea pain in adolescent girls in Program Study Kebidanan Metro Poltekkes Tanjungkarang. Expected acupressure therapy as an easy and practical non-pharmacological method can be used as an alternative treatment in reducing dysmenorrhea pain.